A Split Application Approach to Nitrogen and Growth Regulator Management for Perennial Ryegrass Seed Production. Issue 4 (1st July 2013) - Koeritz, Eric J.; Watkins, Eric; Ehlke, Nancy J.
ABSTRACT: Experiments were conducted during 2009 and 2010 in first year perennial ryegrass ( Lolium perenne L.) fields under limiting or adequate spring N. Three N application methods (single, two‐split, and three‐split), five growth regulators (split and single applications of prohexadione Ca or trinexapac ethyl) and two spring N rates (56 or 100 kg N ha −1 ) were evaluated in a split‐split plot design. Under adequate spring N, all N application methods resulted in similar seed yields but when spring N was limiting, a single application of N resulted in up to 14% greater yield vs. the three‐split. The three‐split N application improved relative chlorophyll index (RCI) 6 to 20% late in the harvest season and reduced stem rust ( Puccinia graminis Pers. subsp. graminicola ) area under the disease progress curve (AUDPC) by 18 to 39% vs. the single N application. Other effects of three‐split N applications observed in 2010 were 8 to 19% less biomass, 2 to 3% greater harvest index (HI), 4% greater seedling vigor, and 25% less lodging. The split prohexadione Ca treatment gave the most consistent results and when vegetative growth was greatest it resulted in a 36% increase in seed yield, a 5.5% increase in HI, 14 cm shorter plants, 70% less lodging, 30% greater RCI, 13% lower stem rust incidence, and 3% lower stem rust severity. Development of a model to optimize rates and timings for split N and growth regulator applications based on growth stage, soil N availability, and growing degree days (GDD) could improve efficacy of split applications.